HUBUNGAN KOMPETENSI PEDAGOGIK DAN MOTIVASI MENGAJAR DENGAN HASIL BELAJAR SISWA KELAS XI PADA MATA PELAJARAN FIKIH DI MAN 2 MODEL MEDAN - hamdani hamdani (Universitas Islam Negeri Sumatera Utara Medan, 2017)
ABSTRACT Professional teachers should equip themselves with a wide range of competences, including pedagogical competence. Mastery of pedagogical competence will facilitate teachers in transferring science and knowledge. Instead they were not in charge, will find it difficult and burdened when transferring knowledge. The initial capital for control of pedagogic competence is not a theory or concept, but motivation. Good competence coupled with high teaching motivation, it will deliver the student at the real achievement of learning objectives. Key words: pedagogic competence, teaching motivation, learning objective